Mα X-ray emission spectrum of multi-ionized Au atoms - Borovoy, M.O.; Ischenko, R.M.; Shiyanovskiy, V.I. (Functional Materials, 2006)
А model of Mα X-ray emission has been proposed taking into account the main vacancy generation and migration channels within the M shell. Equation have been derived allowing the relative intensity calculation of Mα satellites (S(а). For Au, the Sα values under the Mα spectrum excitation by polychromatic emission of BCV-12 X-ray tubes with Cr and Cu anodes have been studied in experiment. The experimental Sα values coincide (within the error limits) with the calculated ones. The model proposed has been concluded to describe correctly the Mα emission in elements having Z>70. Предложена модель рентгеновской Mα-эмиссии, учитывающая основные каналы генерации и миграции вакансий внутри M-оболочки. Получены уравнения, позволяющие рассчитать относительные интенсивности Mα-сателлитов (Sа). Для элемента Au проведено экспериментальное исследование величины Sα при возбуждении Mα-спектра полихроматическим излучением рентгеновских трубок БХВ-12 с Cr и Cu анодами. Экспериментальные и рассчитанные значения величины Sα в пределах погрешности практически совпадают. Сделан вывод о том, что предложенная модель корректна для описания Mα-эмиссии в элементах Z > 70. 3апропоновано модель рентгенiвської Mα-емiсil, яка враховує основнi канали генерацil та мiграцil вакансiй у серединi Mα-оболонки. Отримано рiвняння, що дозволяють розрахувати вiдноснi iнтенсивностi Mα-сателiтiв Sα. Для елемента Au проведено експериментальне дослiдження величини Sα при збудженнi мапектра полiхроматичним випромiнюванням рентгенiвських трубок БXВ-12 з Cr та Cu анодами. Експериментальнi та розрахованi значення величини Sα у межах похибки практично спiвпадають. 3роблено висновок про те, що запропонована модель коректна для опису Mα-емiсil в елементах Z > 70.